2014
DOI: 10.18632/oncotarget.2471
|View full text |Cite
|
Sign up to set email alerts
|

Ciclopirox induces autophagy through reactive oxygen species-mediated activation of JNK signaling pathway

Abstract: Ciclopirox olamine (CPX), a fungicide, has been demonstrated as a potential anticancer agent. However, the underlying anticancer mechanism is not well understood. Here, we found that CPX induced autophagy in human rhabdomyosarcoma (Rh30 and RD) cells. It appeared that CPX-induced autophagy was attributed to induction of reactive oxygen species (ROS), as N-acetyl-L-cysteine (NAC), a ROS scavenger and antioxidant, prevented this process. Furthermore, we observed that CPX induced activation of mitogen-activated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 49 publications
4
57
0
Order By: Relevance
“…In agreement with our findings, a previous 271 study has shown that activation of p38 MAPK contributes to the 272 anti-proliferation effect of b-elemene in glioblastoma cells [15]. 273 Substantial ROS has been found to activate MAPK signaling 274 cascades [28]. Consistent with activation of p38 MAPK, we found 275 that b-elemene treatment caused a significant increase in the 276 production of ROS.…”
supporting
confidence: 86%
“…In agreement with our findings, a previous 271 study has shown that activation of p38 MAPK contributes to the 272 anti-proliferation effect of b-elemene in glioblastoma cells [15]. 273 Substantial ROS has been found to activate MAPK signaling 274 cascades [28]. Consistent with activation of p38 MAPK, we found 275 that b-elemene treatment caused a significant increase in the 276 production of ROS.…”
supporting
confidence: 86%
“…The reason for this discrepancy is unclear, but it may be due to the different cell lines or experimental conditions used. Recent evidence highlights the role of ROS in JNK-activated autophagosome formation (46,47), and ROS has also been reported to be closely associated with HBx-and HBV-mediated biological processes (50,51,61). We therefore further investigated the role of ROS in HBx-activated JNK signaling and autophagosome formation.…”
Section: Discussionmentioning
confidence: 98%
“…Recent work has revealed that ROS may play an important role in JNK-dependent autophagy regulation (46)(47)(48)(49), while HBx treatment has been reported to cause ROS generation in hepatoma cells (50,51). We thus investigated the role of ROS in HBx-induced JNK activation and the ensuing autophagosome formation.…”
mentioning
confidence: 99%
“…CS is a potent source of ROS generation [8,9]. The involvement of ROS in the induction of autophagy has been proven in many studies, as the ROS scavenger and antioxidant can prevent the formation of autophagosomes and the degradation of proteins [10,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%